Hypercalcemia and Renal Affection: An Unusual Initial Presentation of Sarcoidosis - Dzekova Vidimliski, Pavlina; Ristovska, Vesna; Karanfilovski, Vlatko; Severova Andreevska, Galina; Gjorgjievski, Nikola; Nikolov, Igor; Gerasimovska, Biljana; Petrushevska, Gordana (Macedonian Academy of Sciences and Arts/Walter de Gruyter GmbH, 2025)
Sarcoidosis is a chronic, multisystem, inflammatory granulomatous disease that affects multiple organs in the body, but mostly the lungs and the lymph glands. Hypercalcemia and renal affection are rarely initial presenting features, and in the absence of pulmonary symptoms, the diagnosis of sarcoidosis in those patients could be a diagnostic challenge. A case-patient with sarcoidosis presented with elevated serum calcium and creatinine levels. Renal biopsy showed nephrocalcinosis with chronic fibrosing interstitial nephritis. The extensive mediastinal, abdominal, axillar, and neck lymphadenopathy was presented on the computer tomography scan of the patient's chest and abdomen. The neck lymph node surgical biopsy showed confluent, non-caseating, epithelioid granulomas consistent with sarcoidosis. The serum angiotensin-converting enzyme level was elevated. Treatment with oral prednisolone was started, and improvement of renal function and normalization of serum calcium was noted. Sarcoidosis should be considered in the differential diagnoses in patients with renal impairment and non-parathyroid hormone (non-PTH) dependent hypercalcemia.
Keywords: sarcoidosis; hypercalcemia; granulomas; nephrocalcinosis; renal impairment